Tissue tropism and clinical manifestation of chicken infectious bronchitis (review) - Ali Dandal Shebli (Ветеринария сегодня, 2018)
Chicken infectious bronchitis is one of the most important diseases for commercial poultry production. It is regarded generally as a respiratory system disease; different strains of chicken infectious bronchitis virus can demonstrate variability of tissue tropism and affect reproductive organs as well as kidneys with severe effects. Some virus strains propagate in intestines but without pathological changes.